Marketing Innovation for MSMEs Products: Building an Affiliate Marketing-Based Website Using the Waterfall Method - Afandi, Ahmad (AIBPM Publisher, 2023)
The advancement of information technology and the internet has significantly impacted the business world, including Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a crucial role in economic growth, particularly in Asia, as they contribute to a significant portion of exports and serve as key drivers of job creation and income distribution. However, MSMEs require support from various stakeholders to enhance their environmental performance. In the current digital era, having an online presence can be one way for MSMEs to leverage digital technology. An effective approach to expanding marketing reach and increasing product sales for MSMEs is through marketing websites. This research aims to develop a marketing website for an MSME using the Waterfall method, focusing on PT. Keloria Moringa Jaya is a herbal supplement company in Medan, North Sumatra, Indonesia. The study will explore the implementation of Affiliate Marketing in the website development process using the Waterfall method. The research intends to enhance the visibility of PT. Keloria Moringa Jaya's products attract more potential buyers and significantly increase sales. The study also aims to contribute to the literature by enriching the understanding of applying the Affiliate Marketing model in the context of MSMEs. Practical implications of this research include providing guidance and recommendations for other MSMEs interested in developing marketing websites using the Affiliate Marketing model and the Waterfall method.